The printmaking bible the complete guide to materials and techniques - D'Arcy Hughes, Ann; Vernon-Morris, Hebe (Chronicle Books, 2008)
From the Publisher: Perennially popular, printmaking is enjoying a contemporary resurgence but no comprehensive up-to-date manual on the subject exists. At over 400 pages and packed with 1,000 full-color photos and illustrations, The Printmaking Bible is the definitive resource to the ins-and-outs of every variety of serious printmaking technique practiced today. In-depth instructions are accompanied by profiles that show how working artists create their prints. Historical information, troubleshooting tips, and an extensive resource section provide more invaluable tools. Perfect for students, artists, print aficionados, and collectors, this is truly the ultimate volume for anyone involved in this creative and influential art form.